7. MENDAMPINGI ANAK MENONTON "KEKERASAN" TELEVISI - Herieningsih, Sri Widowati (FORUM, 2008)
Television is the most popular medium for children as their source of information and from most study conducted within the influence of media towards children was found that children are categorized as heavy viewers. The condition attached to them as heavy viewers should be put into consideration of parents, especially when it is connected to the fact that TV programs have dominated by violence. However, we should not put the blame solely on television as the effect caused by TV programs also rely on parents involvement in guiding their children whilst watching television. Television in this particular case has tried to give guidance by categorizing their programs, which then should make parents aware to conduct guidance to their children as part of their responsibility. This guiding activity known as parental mediation could take forms in restrictive mediation and evaluative mediation.